Оцінювання як механізм забезпечення якості загальної середньої освіти Фінляндії - Волинець, Людмила (Studies in Comparative Education, 2013)
Стаття присвячена розгляду таких особливостей системи оцінювання якості загальної освіти Фінляндії, як відмова від високого рівня підзвітності та контролю шкіл на основі зовнішнього стандартизованого тестування; використання оцінювання для розвитку та ефективного управління; поєднання оцінювання на національному рівні та самооцінювання на місцевому рівні; уникнення рейтингування шкіл; відмова від підзвітності вчителів; надання процесу оцінювання учнів безпечного, позитивного характеру. Статья посвящена рассмотрению таких особенностей системы оценивания качества общего образования в Финляндии, как отказ от высокого уровня отчетности и контроля школ на основе внешнего стандартизированного тестирования, использование тестирования для развития и еффективного управления, сочетание оценивания на национальном уровне и самооценивания на местном уровне, избежание рейтингования школ, отказ от подотчетности учителей, придание процессу оценивания учиеников безопасного, позитивного характера. The article analyzes peculiarities of the system of education quality evaluation in Finland. These peculiarities act as tools for ensuring education system quality. The first peculiar feature of the Finnish evaluation system is the rejection of the transnational principle of high accountability and control of schools based on external standardized testing. Instead, in Finland, evaluation is used for development and effective management. Evaluation becomes a tool for collection of information needed for analysis and understanding of education system performance and identification of its developmental perspectives in accordance with current environment. The second peculiarity of the Finnish national system of education quality evaluation is the combination of evaluation at the national level and self-evaluation at the local level. The aim of the national evaluation of education results is to track the achievement of the National curriculum goals at the country level. Local self-evaluation by education providers and schools (with active participation of students and parents) is aimed at helping educators to form a holistic and integrated understanding of school performance, ensure effective local governance, and facilitate transparency of school performance for external stakeholders. The avoidance of school rating and competition resulting from comparison with average school results is attributable to the features of the national social culture. In particular, this concerns the principles of complementarity and cooperation. Instead of competition, schools encourage various forms of partnership between teachers, students, parents, schools, and other education participants. Another peculiar feature of the Finnish evaluation system is the replacement of burdensome teacher accountability with teacher responsibility for teaching content and methods. This could be achieved due to the government policy of quality teacher training and trust. Teacher responsibility is realized via the system of quality assurance present in most schools and involving annual discussions of development and evaluation. Finally, the Finnish evaluation system moderately uses student performance evaluation. No marks are used till the age of nine and point scores are introduced only during the sixth year. Instead, there are verbal marks and descriptions of students’ progress in various subjects. There is only one standardized exam at the end of school. Moderate evaluation ensures safety and positiveness of student evaluation process, individualized approach to student education speed and style, realization of student cognitive potential, and responsibility for education achievements.